Arap Belagatı’nda konudan haberdar olan muhataba mesaj iletme amaç ve formları -Kur’an ölçeğinde- - Gezek, Ahmet (My University, 2016)
ET Arapça’da cümle belâgat yönünden haber ve inşâ cümlesi olmak üzere iki kısma ayrılmaktadır. Haber cümlesinin aslî olarak iki gayesi vardır. Çünkü mütekellim muhataba, ya bilinmeyen bir hükmü haber vermektedir ki buna fâide-i haber denilir. Fâide-i haber, ibarenin içerdiği hükmün muhataba fayda sağlaması demektir. Ya da muhataba verilen haberi, mütekellim bildiğini göstermektedir ki buna da lâzım-ı fâide denilir. Lâzım-ı fâidede muhatap, kendisine iletilen haberi önceden bildiğinden dolayı haber kendisine bilgi açısından fayda sağlamaz. Bu durumda haberin faydası yani haberi söyleme amacı, mütekellimin haberi bildiğini göstermesidir. Kur’ân-ı Kerîm bağlamında lâzım-ı fâidenin önemini ortaya koyan bu çalışmamız; giriş, iki ana bölüm ve sonuçtan oluşmaktadır: Bu çalışmada lâzım-ı fâide konusu; klasik dönemden günümüze kadar önemli belâgat kitapları ve tefsirlerin konuyla ilgili açıklamalarından yararlanılmak suretiyle detaylı bir biçimde incelenmeye çalışılmıştır. Girişte genel belâgat terimlerinden önemli bazıları ele alınmıştır. Birinci bölümde tezle ilgili teorik çerçeve, ikinci bölümde Kur’ân-ı Kerîm’den bu bağlamdaki örnekler ve müfessirlerin görüşleri araştırılmış, ulaşılan bulgulara sonuç bölümünde yer verilmiştir. Muhatap, hakkında bilgi sahibi olduğu bir haberi mütekellimden işittiğinde, mütekellimin haberi bildiğini bilmekte olduğundan dolayı lâzım-ı fâide cümleleri, hakiki anlamda haber anlamını içermeyip zımnen içermektedir. Bir müfessirin “lâzım-ı fâide vardır” dediği Kur’ân-ı Kerîm’deki bir haber cümlesine başka bir müfessir âyet-i kerîmenin siyak ve sibakından anladığı manaya göre; kınama, hali öğrenme, zihinde oluşmuş olan soru işaretlerini giderme, Allah (c.c.)’a yönelik olan haberlerde dua makamı, geçmiş hükmü bütün benzerlerine tahakkuk ettirme, cümlenin tazmin ettiği mananın illeti ve ikrarı, ta’rîz / üstü örtülü bir şekilde itiraz ve sitem etme, ikaz kabilinden tekit etme ve özür dileme gibi maksatların olduğunu söyleyebilmiştir. zım-ı fâide, Haber, İnşâ, Belâgat, Müfessir.

In Arabic terms of eloquence sentences are divided into two categories; declarative sentences and construction sentences. There are two basic purposes of declarative sentences. Because our word, either provides to benefit the addressee from the person who makes the declarative sentence / mutekellim, of this kind of declarative sentence that called fâide-i haber. Fâide-i haber, means there is the phrase contained in the provision of the benefit to the interlocutor. Or our word is known from interlocutor that he hearing our word from the person who makes the news / mutekellim, of this kind of declarative sentence that is called lâzım-ı fâide. Interlocutor already knows of the declarative sentence given to him from mutekellim in the lâzım-ı fâide. Therefore it is not the benefit in this kind of news. In this case, the benefit of declarative sentence, in other words the aim of telling the declarative sentence in lâzım-ı fâide show to know the declarative sentence of interlocutors. This thesis consists of introduction, two main sections and a conclusion. In this study, subject necessary benefit / lâzım-ı fâide has been studied in detail by recourse to important rhetoric books and commentaries books of Qur’an from the classical period to the present day. At the entrance some of the general terms of eloquence was investigated. The first chapter related to the theoretical framework of the thesis, in the second chapter the opinions of commentators investigated and examples from the Qur’an in this context. The findings reached are given in the results section. Interlocutor, when he heard a declarative sentence that are knowledgeable about that, from the person who makes the news / mutekellim, he knows that it is familiar with the declarative sentence by mutekellim. Lâzım-ı fâide sentences, it's not news in the true sense, but contains it implicitly. To know the lâzım-ı fâide depends on knowing the fâide-i haber. Commentators that says “the sentence has been lâzım-ı fâide” in the declarative sentence wherein the Holy Qur’an, another commentator has a different purpose to the phrase according to the context of the verse. For example; condemnation, learning, the removal of the question marks that have formed in the mind, pray for the authority that is directed toward Allah on the declarative sentence, similar to the past make it hard for the iv provision of, the reason of the meaning of the sentence contained in, the appeal and reproach in a manner closed, reinforce the sentence, to apologize and etc. meanings they mean. Key words: Lâzım-ı fâide, Declarative sentences, Construction sentences, Eloquence, Commentators of Qur’an.
Keywords: Arap dili ve belagatı; Arap edebiyatı; Edebiyat